2004
DOI: 10.1111/j.1540-627x.2004.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

"Who Done It?" Attributions by Entrepreneurs and Experts of the Factors that Cause and Impede Small Business Success

Abstract: Attribution theory deals with how individuals infer causality between events and has been used to explain various social psychological phenomena such as achievement, sex stereotyping, and the impact of reward on behavior. But the direct application of the theory to entrepreneurship has been made only recently. The present study tests for the existence of a self-serving attribution bias among entrepreneurs when they enumerate the factors that contribute to or impede their business success as well as for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
142
0
34

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(199 citation statements)
references
References 29 publications
9
142
0
34
Order By: Relevance
“…This is referred to as 'self-effacing' bias. In addition, empirical evidence revealed that there are differences in the perception of actors and observers about the cause of an event (Rogoff et al, 2004;Stewart, 2005). Despite these limitations, Kelley and Michela (1980) acknowledges that attribution theory has provided 'meaningful' answers that addresses causal attribution problems.…”
Section: Attribution Theorymentioning
confidence: 99%
“…This is referred to as 'self-effacing' bias. In addition, empirical evidence revealed that there are differences in the perception of actors and observers about the cause of an event (Rogoff et al, 2004;Stewart, 2005). Despite these limitations, Kelley and Michela (1980) acknowledges that attribution theory has provided 'meaningful' answers that addresses causal attribution problems.…”
Section: Attribution Theorymentioning
confidence: 99%
“…Discovering which factors or practices lead to business success and those which lead to failure is a primary -and as yet, unfulfilled -purpose of business research [9]. Therefore, this paper attempts to fill this gap in construction management literature by identifying the success factors for construction businesses from different dimensions, that is, from the perspective of the entrepreneurship theory.…”
Section: Introductionmentioning
confidence: 99%
“…The first one specifies the internal and external factors and the second one the factors that are related to the owner-manager, to the business itself and to the environment (Bruderl et al 1992;Machado and Espinha 2005;Rogoff et al 2004;Sten 1998;Zacharakis et al 1999).…”
Section: Mortality Factors: An Overviewmentioning
confidence: 99%
“…The external factors are those conditions or powers that are outside the businessman's control: economy, government regulations, and so on (Rogoff et al 2004). …”
Section: Mortality Factors: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation